EZ Pot / Muhammad Hairun Eman Mohammad Zaki ... [et al.] - Mohammad Zaki, Muhammad Hairun Eman; Musi, Suhaila; Mohamad@Zaini, Zairul Firdaus; Jumain, Muhammad Adil; Nasarudin, Siti Nur Syahirah; Muhammad Azrul Aidi Philips, Muhammad Azdy Haiqal (2023)
EZ eco aims to develop a new high-tech product, the EZ pot, a self-watering vase with unique features that make it more eco-friendly and convenient. Since a standard flower pot needs human effort to take care of, the idea of an EZ pot comes from there. We reduce human work to monitor their plant 24/7. Our objective is to help plantsman, workaholics, and busy and aesthetic people to take care of their plants. Besides, EZ pots are also suitable to use for people who want to start home gardening. This pot is also designed to prevent pollution. EZ Pot is made with modern solar electricity technology that uses solar energy as its primary source and comes in six different colours. This product is designed with a solar panel as the main power supply instead of electric to make it wireless and futuristic looks. Secondly, a timer where Customers can set up a timer which will automatically water plants. Thirdly, a digital clock with an elegant design. Fourthly, a water tank made of blow moulding plastic that can store up to 1.0L of water—fifthly, a humidifying sensor embedded in the pot to sense humidity level, wire, and lastly, a water pump to supply water to the pump. We added these complicated components as a competitive advantage to ensure our product is long lasting in today's market. Our company focuses on offering our product, EZ Pot, to four demographics: workaholics, travellers, students and educators. For profitability, our company will use various marketing techniques such as selling the product offline and online buying and selling applications such as the shoppe, Lazada and TikTok platforms. For the management aspect, each consists of a general manager, administration manager, marketing, production manager, operational manager and financial manager. Each manager has abilities and specific roles in managing the company in all aspects.